(untitled) (AYUSHDHARA, 2022)
Cerebellar ataxia is a form of ataxia originating in the cerebellum (the part of brain that is incharge of balance and coordination). Cerebellar ataxia can occur as a result of many diseases and may present with symptoms of inability to coordinate balance, gait, extremity and eye movements. In cerebellar ataxia progressive atrophy of cerebellum occurs. This can be compared to Mastulungshya in Ayurveda. Case Presentation- A 27 years male adult with the complaint of difficulty in walking, writing and difficulty in speaking since two years and also inability in doing daily activities of life got admitted in the Panchkarma male ward. On the basis of clinical features and investigation reports of MRI and CT of the brain, diagnosis done was Spino-Cerebellar ataxia. Management and Outcome- Aacharya Chakrapaani told that Mastishkya as Shirogata sneha (ca.sha 7/15) and atrophy means Kshya of Shirogata sneha. Patient was treated according to above principle, Brihana Chikitsa along Panchkarma procedures like Mustaadi yapna basti and Sarvang abhyang and Shashtikshali pindswedan was done for one month. Significant improvement was seen in clinical features. Patient walking distance increased from 100 meters to 2-3km daily without fatigue. BARS score was reduced from 12 to 6. His speech was improved and easily understandable. Discussion- In the present case, already damaged part was not recovered but the further progressive damage was prevented. Also there was significant improvement in clinical features. Ayurveda says Vyadhiviprit chikitsa sidhaant i.e., Brihana chikitsa in Kshyapradhan vyadhi. The Vyadhinidaan according to Ayurveda sidhant and treating them accordingly may be helpful in many neurological disorders.